Artificial pinning centers in MgB2 superconducting bulks - Da Silva, L.B.S. (2020)
The optimization of MgB2 superconducting properties is extremely important for practical application. The introduction of an effective artificial pinning center in this material can enhance its critical current density efficiently. In this paper, VB2 is described as a material that provides effective pinning in the MgB2 bulks. The simultaneous addition of SiC as a carbon source is also analyzed. The samples were prepared using ball milling under a controlled atmosphere and heat treatment with a continuous argon flux. As a result, the superconducting properties could be optimized due to the effective improvement in the pinning behavior as well as with the carbon doping.